The Role of KUA Meral District, Karimun Regency, in Minimizing Underhanded Marriage Practices (Siri Marriage) - Nur Aziz; Uum Ummul Muhaimah (IRDH International Journal of Social Sciences & Humanities, 2025)
The phenomenon of unofficial marriages still poses a serious challenge in Meral District, Karimun Regency. This practice, which is deemed valid according to religion, is often chosen as a quick and cheap alternative without considering the legal and social impacts, particularly for women and children. This research aims to analyze the role of the KUA (Office of Religious Affairs) in Meral District in minimizing the practice of unregistered marriages, identifying the obstacles faced, and formulating a more adaptive follow-up strategy. A qualitative approach is used through observations, in-depth interviews with religious counselors, community leaders, couples in unregistered marriages, and analysis of official KUA documents. The research findings indicate that the main obstacles include limited human resources, inadequate educational facilities, strong cultural influences, and low legal literacy among the community. The proposed strategic recommendations include increasing and strengthening the capacity of religious counselors, digitizing educational materials, implementing contextual cultural-based approaches, and enhancing cross-sector collaboration with schools, community health centers, and village authorities. These efforts are expected to gradually raise legal awareness and reduce the practice of unregistered marriages, thereby better ensuring the protection of women's and children's rights.